2020
DOI: 10.1071/an19281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flemingia macrophylla silage on in vitro fermentation characteristics and reduced methane production

Abstract: Fodder shrub, Flemingia macrophylla silage (FMS), was nutritionally evaluated for rumen fermentation characteristics using an in vitro gas production technique. Dietary treatments were imposed in a 2 × 7 factorial arrangement in a completely randomised design. The first factor was two ratios of roughage:concentrate (R:C at 60:40 and 40:60), and the second factor was seven levels of FMS supplementation at 0, 20, 40, 60, 80, 100 and 120 g/kg of dietary substrate. The results revealed that a R:C ratio at 40:60 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…With an increasing concentrate proportion, the in vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD) increased (p < 0.05). These findings agree with Viennasay et al [33], regarding improving in vitro digestibility by increasing the proportion of concentrates in the diet. This could be due to the concurrent induction of microbial growth, which improved digestibility.…”
Section: In Vitro Digestibilitysupporting
confidence: 93%
See 2 more Smart Citations
“…With an increasing concentrate proportion, the in vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD) increased (p < 0.05). These findings agree with Viennasay et al [33], regarding improving in vitro digestibility by increasing the proportion of concentrates in the diet. This could be due to the concurrent induction of microbial growth, which improved digestibility.…”
Section: In Vitro Digestibilitysupporting
confidence: 93%
“…There was no interaction effect between the R:C ratio and the addition of MSLP on overall VFA and VFA profiles (Table 4). The total concentrations of VFA ranged from 40.1 to 49.7 mM, which was similar to the findings of Kang et al [39] and Viennasay et al [33]. The R:C ratio at 40:60 increased total VFA and C 3 , but lowered C 2 and the C 2 :C 3 ratios (p < 0.05).…”
Section: Volatile Fatty Acid and Methane Productionsupporting
confidence: 89%
See 1 more Smart Citation
“…Increasing the proportion of red clover silage to orchardgrass linearly reduced CH 4 emissions per unit of dry matter intake in sheep [49]. Increasing the level of Flemingia macrophylla silage supplementation in rice straw-based diets decreased in vitro CH 4 emissions and was accompanied by a decrease in protozoa population [39]. The use of this tannin-containing local fodder shrub in silage has also been shown to improve nutrient digestibility, rumen fermentation efficiency, and milk production in lactating dairy cows [50].…”
Section: Increasing Nutrient Use Efficiency and Animal Performances In Ruminantsmentioning
confidence: 99%
“…Various experimental results have shown that tannins in silage could modify rumen fermentation and proteolysis. For instance, increasing supplementation level of Flemingia macrophylla silage, a tropical shrub legume containing condensed tannins, reduced in vitro ruminal NH 3 concentration in both high-roughage and low-roughage diets [39]. Apart from being natively present in the material ensiled, tannins can also be added to silage to modulate fermentation processes.…”
Section: Increasing Nutrient Use Efficiency and Animal Performances In Ruminantsmentioning
confidence: 99%